The curious incident of wisdom in the thought of Feng Qi (1915–1995): comparative philosophy, historical materialism, and metaphysics. Issue 3 (3rd July 2018) - Van den Stock, Ady
ABSTRACT: After some introductory remarks on the work of the modern Chinese philosopher Feng Qi, I begin this article by providing some observations concerning the ambiguous notion of 'wisdom' in Orientalist representations of non-Western thought and in comparative philosophy, as well as on the peculiar form of subjectivity ascribed to the 'wise' subject. I then proceed by offering an account of Feng's philosophical universalism and historical materialist outlook, outlining the identification of wisdom with metaphysics in his early work and exploring the status and function of wisdom in his mature writings. In doing so, I analyze the tension in Feng's work between the theoretical rationality and systematicity of 'metaphysics' on the one hand and the existential and transformative orientation of 'wisdom' on the other.